PENGARUH PEMBELAJARAN PAKEM DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPA KELAS V SDN MAGETAN 1 DAN SDN MAGETAN 2 KABUPATEN MAGETAN - Suryati Suryati (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
The development of science and technology has a huge influence on improving the quality of education. It needs the supporting components, including teachers, students, facilities and infrastructure, even concerning the curriculum. It thus requires the ability of the teachers in designing learning model that is more student-centered, according to the characteristics of the field of study and student characteristics in order to achieve maximum results. This study is anexperimental study which involving 60 students as the sample. The study sample was obtained by means of purposive sampling. Moderate research data obtained by distributing questionnaires and tests to provide a sample. The data analysis technique used is the analysis of variance of two paths. Based on the data calculation results are obtained as follows : 1) There is a differencebetween PAKEM method and lecture method with learning result in Natural science of fifth students SDN Magetan 1 and SDN Magetan 2 academic year 2013/2014, which have active and creative learning outcomes, which shown by F value greater then F table , namely (4.654 > 3.99). 2) There is a difference in learning result in science classes of SDN Magetan 1 and SDN Magetan 2 academic year 2013/2014 which has a high learning motivation and low learning motivation, the significant differences indicated greater count dengan nilai FB F table, ie (27943 > 3.99). 3) There is an interaction between learning and teaching using lectures PAKEM with motivation toward science learning outcomes SDN Magetan class 1 and 2 Magetan SDN Magetan academic year2013/2014, which implements active and creative learning classes to students who are highly motivated to have the results learn science better when compared with the results of science learning in students with learning other lectures with low motivation , and is also indicated by the calculated F is greater than F table, namely (12,859 > 3.99).